Prototype Alat Pengecekan dan Penyortir Kesegaran Cabai Berdasarkan Warna Menggunakan Sensor Tcs230 Berbasis Arduino - Elsa Indah Sari; Suhada Suhada; Fitri Anggraini; Dedy Hartama; Ika Okta Kirana (BEES: Bulletin of Electrical and Electronics Engineering, 2021)
This study aims to create an arduino- based tool to determine the freshness of red chillies using the TCS230 color sensor to facilitate chilli traders, supermarkets and markets in choosing good and bad quality based on the color of chili. Fresh chili will be red while the bad ones are usually dull red, slightly brownish and yellowish. TCS230 converts the color of light to fermentation with a square signal output with a frequency that is proportional to the current. The working principle is that the chili passes through the TCS230 sensor from the display of this tool, it will be seen the amount of color based on the specified chili criteria will produce chili output through checking and sorting the chillies of good and bad quality.